STRATEGI KOMUNIKASI INTERPERSONAL KYAI DALAM MEMBENTUK KARAKTER ISLAMI SANTRI:STUDI KUALITATIF DI PONDOK PESANTREN AL-MUSYARROFAH PETUKANGAN UTARA - NIA FARHANIS; IDHAM JAUHARI; DELI AMARTA (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the interpersonal communication strategies employed by the Kyai in shaping the Islamic character of students at Al-Musyarrofah Islamic Boarding School, Petukangan Utara, as well as to identify the supporting and inhibiting factors in their implementation. The study employed a descriptive qualitative approach. Data were collected through semi-structured interviews, observation, and documentation, involving the Kyai, caregivers/ustadz, and students as informants. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the Kyai’s interpersonal communication strategies in shaping the Islamic character of students are implemented through three main forms: advice and motivation, role modeling, and reprimands and discipline. Advice and motivation are used to provide understanding and encouragement while fostering students’ awareness of Islamic values. Role modeling is demonstrated through the Kyai’s actual behavior in daily life, particularly in showing manners, discipline, responsibility, and consistency between words and actions. Meanwhile, reprimands and discipline are used to guide and correct students’ behavior that does not conform to the values and rules of the Islamic boarding school. Based on the analysis of interpersonal communication control strategy theory, these three strategies are related to the dangling carrot, catalyst, and hanging sword strategies, respectively. The supporting factors of interpersonal communication include trust, openness, empathy, a supportive attitude, equality, and a conducive environment. The inhibiting factors include differences in perception, differences in students’ backgrounds, and psychological barriers. These communication strategies contribute to the development of students’ Islamic character, as reflected in manners, discipline, responsibility, politeness, and the practice of Islamic values in everyday life